A new species of Campanula L. (Campanulaceae) from Western Himalaya, India - Balkrishna, Acharya; Singh, Harsh; Joshi, Bhasker; Srivastava, Anupam; Kumar, Aashish; Kumar, Amit; Vats, Prashant; Singh, Vikram; Mishra, Rajesh Kumar (Phytotaxa, 2024)
A new species Campanula densiciliata from Yamunotri, Uttarakhand is described and illustrated. The new species is closely related with other previously described species namely, Campanula argyrotricha and C. latifolia but, differ in its rounded leaf base with sinuate margins, much reduced calyx teeth less than half of the corolla with crenate margin, elliptic corolla lobes and different lengths of stigmatic lobes. The new species is found in humus rich soil under Rhododendron forest.